Organizational citizenship behavior guru : Seberapa besar peran budaya organisasi ? - Pratiwi, Mita Fauziyah; Sofiah, Diah; Muslikah, Etik Darul (SUKMA : Jurnal Penelitian Psikologi, 2025)
This study examines the relationship between organizational culture and organizational citizenship behavior among teachers at vocational high schools in Surabaya. Active teacher involvement is a challenge in improving the effectiveness of schools as educational organizations. This study aims to determine the extent to which organizational culture is related to teachers' organizational citizenship behavior. This study used a quantitative correlational approach. The study population consisted of 110 vocational high school teachers in Surabaya, with 86 respondents being selected using a random sampling technique. The data collection instrument was a questionnaire with a rating scale that has been tested for validity and reliability. There is a positive and significant relationship between organizational culture and organizational citizenship behavior, meaning that the stronger the organizational culture, the higher the organizational citizenship behavior among teachers. This finding emphasizes the importance of strengthening organizational culture as a strategy to encourage teacher involvement. Building a strong organizational culture can be a strategic step in improving the quality of human resources and organizational effectiveness at the school level. Penelitian ini membahas hubungan budaya organisasi dan perilaku kewargaan organisasi pada guru di sekolah menengah kejuruan di surabaya. Keterlibatan aktif guru menjadi tantangan dalam meningkatkan efektivitas sekolah sebagai organisasi Pendidikan. Adanya penelitian ini untuk mengetahui sejauh mana budaya organisasi berhubungan dengan perilaku kewargaan organisasi guru. Penelitian ini menggunakan pendekatan kuantitatif korelasional .Populasi penelitian berjumlah 110 yang merupakan guru sekolah menengah kejuruan di surabaya dengan sampel yang diambil adalah 86 responden menggunakan Teknik random sampling. Instrumen pengumpulan data berupa kuesioner dengan skala penilaian yang telah teruji validitas dan reliabilitasnya. Adanya hubungan positif dan signifikan antara budaya organisasi dan perilaku kewargaan organisasi, atau semakin tinggi budaya organisasi maka semakin tinggi perilaku kewargaan organisasi pada guru. Temuan ini menekankan pentingnya penguatan budaya organisasi sebagai strategi untuk mendorong keterlibatan guru sehingga membangun budaya organisasi yang kuat dapat menjadi langkah strategis dalam meningkatkan kualitas sumber daya manusia dan efektivitas organisasi di tingkat sekolah.